The Usefulness of Spinal Cord Stimulation for Chronic Pain Due to Combined Vasospastic Prinzmetal Angina and Diabetic Neuropathic Pain of the Lower Limbs - Kinfe, Thomas M.; Pintea, Bogdan (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2016)
Objective To describe an unusual case of combined neuropathic and ischemia-induced chronic pain in a patient who was treated with one high thoracic paddle lead.Background To the best of our knowledge, the use of spinal cord stimulation (SCS) utilizing a single lead as a treatment strategy for combined Prinzmetal angina, a cardiac ischemia-induced disturbance of nociceptive perception, and diabetic neuropathy of the lower limbs has rarely been described.Case Report The underlying pain conditions and SCS technique used to treat both types of pain—Prinzmetal angina and lower-limb diabetic neuropathy—in a 73-year-old patient experiencing medical or interventional refractory complex pain syndrome are described. The SCS electrode was placed in the anatomical midline with a T2- to T3-level laminotomy and externalized for postoperative trial stimulation with systemic antibiotic administration.Results After 8 months, stable pain control was achieved. No complications occurred.Conclusion We present a chronic pain syndrome due to combined Prinzmetal angina and diabetic neuropathy of the lower limbs with sustained pain relief utilizing a single SCS lead.
Keywords: spinal cord stimulation; ischemic cardiac pain; diabetic neuropathy